ANALISIS SISTEM PENGENDALIAN INTERNAL ATAS PIUTANG USAHA DALAM MEMINIMALKAN PIUTANG TAK TERTAGIH PADA PT. TRANS CIBUBUR PROPERTY - Setiadi1; Winona Ramadhanti Adawiyah 2 (Fakultas Ekonomi dan Bisnis, Universitas Jayabaya, 2025)
Accounts receivable represents a crucial asset component affecting company liquidity and financial performance. This research aims to analyze the effectiveness of internal control systems over accounts receivable in minimizing bad debts at PT. Trans Cibubur Property. The research methodology employs a qualitative approach using participant observation, in-depth interviews, and document analysis. The researcher served as a collection staff in the Finance- Account Receivable (AR) department to directly observe internal control system implementation. The COSO (Committee of Sponsoring Organizations of the Treadway Commission) Framework is utilized as the analytical foundation, encompassing five components: control environment, risk assessment, control activities, information and communication, and monitoring. Results indicate that PT. Trans Cibubur Property has implemented a comprehensive internal control system. Historical data from 2018-2021 shows a decrease in bad debt rates from 37% (Rp 885,242,846) in 2018 to 17% (Rp 5,055,894,278) in 2021, despite total receivables increasing from Rp 2.4 billion to Rp 30.5 billion. Implementation of the five COSO Framework components functions well, though improvement areas remain, including procedure standardization, enhanced staff training, and predictive technology implementation. The research concludes that effective internal control systems play a vital role in minimizing bad debt risks and maintaining corporate financial health.Keywords: Internal Control System, Accounts Receivable, Bad Debts, COSO Framework, Risk Management